2021
DOI: 10.1002/brb3.2452
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety symptoms and perceived stress in health professionals in the context of COVID‐19: Do adverse childhood experiences have a modulating effect?

Abstract: Background: Adverse childhood experiences (ACE) have a great impact on mental health outcomes of adults. However, little is known whether ACE may act as modulators of the mental health of health professionals caring for patients with COVID-19.Methods: Data were collected through an online cross-sectional survey administered to health professionals in Lima (Peru) between May and July 2020. The survey included standardized self-assessment instruments for anxiety, depression, acute stress (AS) and history of ACE.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“… 58 A recent study showed that a history of early sexual abuse increased the risk for anxiety in health professionals caring for patients with COVID‐19. 59 The results of the present study are also consistent with several studies showing levels of anxiety during the COVID-19 pandemic to be positively correlated with levels of insomnia and other indices of poor sleep quality. 10 , 21 , 22 Nevertheless, we also found some direct effects, with greater morbidity-mortality exposure, financial difficulties, and adverse experiences in childhood uniquely predicting greater sleep difficulties during COVID-19, above and beyond general levels of anxiety surrounding the pandemic.…”
Section: Discussionsupporting
confidence: 92%
“… 58 A recent study showed that a history of early sexual abuse increased the risk for anxiety in health professionals caring for patients with COVID‐19. 59 The results of the present study are also consistent with several studies showing levels of anxiety during the COVID-19 pandemic to be positively correlated with levels of insomnia and other indices of poor sleep quality. 10 , 21 , 22 Nevertheless, we also found some direct effects, with greater morbidity-mortality exposure, financial difficulties, and adverse experiences in childhood uniquely predicting greater sleep difficulties during COVID-19, above and beyond general levels of anxiety surrounding the pandemic.…”
Section: Discussionsupporting
confidence: 92%
“…This study is part of the Mental Health of Healthcare Workers project, which was conducted during the pandemic in the city of Lima, Peru, in the months of May and June 2020. The project consisted of a survey to measure aspects of mental health related to the context of the pandemic that allowed an exploration of the influence of the pandemic context on the mental health of HP; the results were published at the end of 2021 (Fernández‐Arana et al., 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…These working conditions, added to the impact of the pandemic on the quality of life of HP, could explain why when faced with COVID‐19 on the front line, the mental health of HP was affected (Fernández‐Arana et al., 2022 ; Lozano‐Vargas, 2020 ; Pearman et al., 2020 ; Siddiqui et al., 2021 ; Vizheh et al., 2020 ), diminishing their capacity for clinical understanding and/or their decision‐making skills (Young et al., 2021 ). Therefore, we must consider the COVID‐19 pandemic as a potent and persistent stressor and that its effects on the mental health of HP depended on, among other factors, the discomfort experienced as a result of poor working conditions and feelings of abandonment by their governments associated with precarious health services (HS) that failed in their duty to protect them ( Caring for people who care: supporting health workers during the COVID 19 pandemic—eClinicalMedicine , s. f .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This context, added to the impact on quality of life, explains why the mental health of the HP who faced COVID‐19 on the front line (Pearman et al., 2020 ; Shanafelt et al., 2020 ; Vizheh et al., 2020 ) was affected, leading to a deterioration in their clinical understanding capacities and/or decision‐making skills (Siddiqui et al., 2021 ). Consequently, the COVID‐19 pandemic must be considered a powerful and persistent stressor, whose effects on the mental health of HP stem from (Ambrosetti et al., 2021 ; Amerio et al., 2021 ; Nobari et al., 2021 ) among other factors, the discomfort experienced as a result of precarious working conditions and feelings of being abandoned by health authorities who did not comply with the duty to protect them (Charney et al., 2020 ; Crocker et al., 2023 ; Editorial eClinicalMedicine, 2020 ; Fernández‐Arana et al., 2022 ; Lin et al., 2020 ; Olórtegui‐Yzú et al., 2023 ; Organización Panamericana de la Salud, 2022 ; Young et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%